REVITALISASI PERAN PEREMPUAN DI WILAYAH PUBLIK MENURUT FATIMA MERNISSI - BONITA IZWANY (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2020)
This research is to find out the background and problem formulation ofFatima Mernissi's thoughts, know Fatima Mernissi's views on the position androle of women, and analyze the conception of Fatima Mernissi with concepts inIslam. The author uses the method of interpretation to analyze data, and the formof this study is a Library Research. The data that the authors use in this study isdivided into primary and secondary data. The primary data to be used as a sourceof reference is the book of the Position of Women in Islam which is the work andthoughts of Fatima Mernissi. While the secondary data are books and internetmedia related to the topic of discussion. From the research conducted it can beconcluded that Fatima Mernissi is a figure who advocates a re-examination of thetrue Islamic concept of the role of women, especially in public life, becauseMernissi found a tendency for patriarchal cultural influences from male ulama intranslating the message of Islam. Fatima Mernissi also voiced the importance ofthe struggle of the woman herself is fighting for her life to achieve a better qualityof life without forgetting her nature as a woman. Thus it can be concluded that theconcept obtained is the concept of leadership according to Islam and the analysisof Fatima Mernissi's thought which is balanced and mutually compatible. Womenare not limited to doctrines that curb women in their scope. Then the whole ideaof Fatima Mernissi is starting from the effort to find the point of problems facedby women, and to lift the position of women from patriarchal bias andmisogynism. The issue of women must be considered at this time, women mustrise, using the guarantee of freedom given. With the best, especially showing theidentity of women to become a leader because women are equal to men